A basic magnesium carbonate nanofiber adsorbent and its preparation method and application
By reacting magnesium carbonate trihydrate with citric acid under specific conditions, basic magnesium carbonate nanofiber adsorbent was prepared, which solved the problems of high cost and low adsorption capacity of norfloxacin adsorbent in the prior art, and achieved efficient and low-cost norfloxacin removal effect.
Patent Information
- Application Number
- CN202510045012.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing norfloxacin adsorbents have high preparation cost, complex process and low adsorption capacity, making it difficult to efficiently remove norfloxacin from water bodies.
The reaction of magnesium carbonate trihydrate and citric acid under specific ratios and conditions was made to prepare a basic magnesium carbonate nanofiber adsorbent, which has nano-scale fiber morphology and high adsorption capacity.
The alkaline magnesium carbonate nanofiber adsorbent prepared with low cost and simple process has the ability to efficiently adsorb norfloxacin, with a removal rate of up to 92%, and a maximum adsorption amount of 3333.33 mg/g.
Smart Images

Figure CN119425612B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of adsorption materials and restoration of polluted water bodies, and specifically relates to a basic magnesium carbonate nanofiber adsorbent and a preparation method and application thereof. Background Art
[0002] Norfloxacin is a type of antibiotic widely used in veterinary medicine and human disease treatment. Since only a small portion of antibiotics can be absorbed by the human body, the remaining antibiotics are excreted through urine and exposed to water and soil environments. Norfloxacin in water can make bacteria resistant and may threaten human health through the food chain. Therefore, norfloxacin is currently listed as one of the new pollutants under key control.
[0003] Existing treatment methods for norfloxacin include: photocatalysis, electrocatalysis, ultrasonic degradation and adsorption, among which adsorption is an effective removal method. At present, norfloxacin adsorbents mainly include porous resins, gels, carbon nanotubes, Mg-Al double-layer hydroxides and zeolites. However, the norfloxacin adsorbents prepared by the above-mentioned prior art have high preparation costs, complex preparation processes and low adsorption capacity, all of which limit the efficient removal of norfloxacin in water. Summary of the invention
[0004] In view of the shortcomings of the above-mentioned prior art, the present invention provides a basic magnesium carbonate nanofiber adsorbent and a preparation method and application thereof. The present invention uses magnesium carbonate trihydrate as a reactant and converts magnesium carbonate trihydrate into a basic magnesium carbonate nanofiber adsorbent under the action of citric acid. The preparation method of the present invention is simple and has low production cost, and the obtained basic magnesium carbonate nanofiber adsorbent has high adsorption capacity for norfloxacin.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] A method for preparing a basic magnesium carbonate nanofiber adsorbent comprises the following steps:
[0007] Magnesium carbonate trihydrate is used as a reactant, and magnesium carbonate trihydrate and citric acid are mixed in water. Citric acid can chelate free magnesium ions in the reaction system, thereby reducing the concentration of free magnesium ions. Low magnesium ion concentration is conducive to the formation of basic magnesium carbonate nanofiber crystal nuclei, so that magnesium carbonate trihydrate reacts under the regulation of citric acid and is converted into a basic magnesium carbonate nanofiber adsorbent with a nanofiber morphology.
[0008] Preferably, the mass ratio of citric acid to magnesium carbonate trihydrate is 0.04-0.1: 1. Too little citric acid has limited regulatory effect on the conversion of magnesium carbonate trihydrate to basic magnesium carbonate nanofiber adsorbent, and fibrous basic magnesium carbonate cannot be generated; too much citric acid will increase production costs.
[0009] Preferably, the mass ratio of magnesium carbonate trihydrate to deionized water is 0.01 to 0.06: 1. If the amount of deionized water is too low, the molar ratio of MgCO3, Mg(OH)2 and H2O in the generated basic magnesium carbonate nanofiber adsorbent is not 4:1:5, while too much deionized water will lead to a decrease in production efficiency.
[0010] Preferably, the reaction conditions for preparing the basic magnesium carbonate nanofiber adsorbent are: stirring the reaction at 70°C to 95°C for 6h to 18h. If the time is too short, the nanofibers of the basic magnesium carbonate nanofiber adsorbent will not grow completely, and if the time is too long, the morphology will hardly change. Based on efficiency considerations, 6h to 18h is determined; if the temperature is too low, nanofibers cannot be grown, and if the temperature is too high, the molar ratio of MgCO3, Mg(OH)2 and H2O in the generated basic magnesium carbonate is not 4:1:5.
[0011] Preferably, magnesium carbonate trihydrate is prepared according to the following steps: using a soluble magnesium salt and a soluble carbonate as raw materials, mixing the soluble magnesium salt and the soluble carbonate in deionized water and reacting them, and then filtering and washing with water until neutral to obtain magnesium carbonate trihydrate.
[0012] Preferably, the soluble magnesium salt Mg 2+ CO3 with soluble carbonates 2− The molar ratio is 1:1.
[0013] Preferably, the reaction conditions for preparing magnesium carbonate trihydrate are: stirring the reaction at room temperature for 0.5h to 2h.
[0014] The invention also protects the basic magnesium carbonate nanofiber adsorbent prepared by the preparation method. The basic magnesium carbonate nanofiber adsorbent is composed of MgCO3, Mg(OH)2 and H2O in a molar ratio of 4:1:5.
[0015] Preferably, the diameter of the basic magnesium carbonate nanofiber adsorbent is 3 nm to 70 nm.
[0016] The invention also protects the use of the basic magnesium carbonate nanofiber adsorbent in the preparation of the norfloxacin adsorbent.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention uses magnesium carbonate trihydrate as a reactant and citric acid as a regulating agent. The mass ratio of citric acid to magnesium carbonate trihydrate is 0.04-0.1:1, and the mass ratio of magnesium carbonate trihydrate to deionized water is 0.01-0.06:1. Under the regulating action of citric acid, magnesium carbonate trihydrate is converted into a basic magnesium carbonate nanofiber adsorbent. No other impurities are generated during the preparation process. The preparation method is simple, the raw materials are cheap and easily available, and the production cost is low.
[0019] In the basic magnesium carbonate nanofiber adsorbent prepared by the method of the present invention, the basic magnesium carbonate is composed of MgCO3, Mg(OH)2 and H2O in a molar ratio of 4:1:5, and is recorded as 415-type basic magnesium carbonate. The basic magnesium carbonate in the prior art is mostly 414-type basic magnesium carbonate, that is, composed of MgCO3, Mg(OH)2 and H2O in a molar ratio of 4:1:4. Compared with the 414-type basic magnesium carbonate in the prior art, the 415-type basic magnesium carbonate of the present invention has a different crystal structure and therefore has a different morphology. The 414-type basic magnesium carbonate is a micron-scale spherical morphology, while the 415-type basic magnesium carbonate of the present invention is a fiber morphology with a nanometer-scale diameter. Compared with the micron-scale spherical morphology of the existing 414-type basic magnesium carbonate, the nanofiber has a larger specific surface area, and therefore has a higher adsorption capacity for norfloxacin.
[0020] 2. The basic magnesium carbonate nanofiber adsorbent of the present invention is used as a norfloxacin adsorbent, and adsorption experiments are carried out in norfloxacin solutions of different concentrations. The basic magnesium carbonate nanofiber adsorbent can reach adsorption equilibrium within 15 minutes, and the norfloxacin removal rate is as high as 92%. Through fitting, it is concluded that the maximum adsorption capacity of the basic magnesium carbonate nanofiber adsorbent for norfloxacin is 3333.33 mg / g, which is the maximum adsorption capacity of norfloxacin compared with current research results. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a morphology diagram of the basic magnesium carbonate nanofiber adsorbent of Example 1.
[0022] Figure 2 This is the XRD diagram of the basic magnesium carbonate nanofiber adsorbent of Example 1.
[0023] Figure 3 This is a graph showing the adsorption capacity and efficiency of the basic magnesium carbonate nanofiber adsorbent of Example 1 for norfloxacin.
[0024] Figure 4 This is a morphology diagram of the basic magnesium carbonate nanofiber adsorbent of Example 2.
[0025] Figure 5 This is the XRD diagram of the basic magnesium carbonate nanofiber adsorbent of Example 2.
[0026] Figure 6 This is a graph showing the adsorption capacity and efficiency of the basic magnesium carbonate nanofiber adsorbent of Example 2 for norfloxacin.
[0027] Figure 7 This is a graph showing the cyclic adsorption performance of the basic magnesium carbonate nanofiber adsorbent of Example 2 for norfloxacin.
[0028] Figure 8This is a graph showing the adsorption capacity of the basic magnesium carbonate nanofiber adsorbent of Example 2 in norfloxacin solutions of different concentrations.
[0029] Fig. 9 The Langmuir fitting diagram of the adsorption of norfloxacin by the basic magnesium carbonate nanofiber adsorbent of Example 2 is shown.
[0030] Fig.10 This is the morphology of the product of Comparative Example 1.
[0031] Fig.11 This is the morphology of the product of Comparative Example 2. DETAILED DESCRIPTION
[0032] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0033] In view of the problems of high preparation cost and low adsorption capacity of norfloxacin in current norfloxacin adsorbents, the present invention provides a basic magnesium carbonate nanofiber adsorbent, namely nanofibers of 415-type basic magnesium carbonate. The 415-type basic magnesium carbonate prepared by the method of the present invention has good stability. When the prepared 415-type basic magnesium carbonate is used to remove norfloxacin in water, it has excellent adsorption performance.
[0034] The good stability of the basic magnesium carbonate nanofiber adsorbent was proved by conducting cyclic adsorption experiments, and the excellent adsorption performance of the basic magnesium carbonate nanofiber adsorbent was proved by comparing the maximum adsorption amount with other existing adsorbents.
[0035] The technical solution of the present invention is further studied by using embodiments and comparative examples below. The specific research methods and results are as follows:
[0036] Example 1
[0037] A method for preparing a basic magnesium carbonate nanofiber adsorbent comprises the following steps:
[0038] Step 1: Add 50 mL of 2.25 mol / L sodium carbonate solution to 50 mL of magnesium chloride solution. 2+ CO3 in sodium carbonate solution 2− The molar ratio is 1:1, the solvents of the magnesium chloride solution and the sodium carbonate solution are both deionized water, and then the reaction is stirred for 0.5 hours. After the reaction is completed, it is filtered and washed with deionized water to a pH value of 7.0, and then dried at 50°C for 12 hours to obtain magnesium carbonate trihydrate.
[0039] Step 2: Take 2 g of magnesium carbonate trihydrate from step 1, mix it with 0.08 g of citric acid in 100 mL of deionized water by ultrasonic and mechanical stirring, then place it in a three-necked flask, react at 80 ° C for 8 hours, cool it naturally to room temperature, filter it, wash it with deionized water, and dry it at 50 ° C for 12 hours to obtain a basic magnesium carbonate nanofiber adsorbent.
[0040] Example 2
[0041] A method for preparing a basic magnesium carbonate nanofiber adsorbent comprises the following steps:
[0042] Step 1: Add 50 mL of 2.25 mol / L sodium carbonate solution to 50 mL of magnesium sulfate solution. 2+ CO3 in sodium carbonate solution 2− The molar ratio is 1:1, the solvents of the magnesium sulfate solution and the sodium carbonate solution are both deionized water, and then the reaction is stirred for 0.5 hours. After the reaction is completed, it is filtered and washed with deionized water to a pH value of 7.0, and then dried at 50°C for 12 hours to obtain magnesium carbonate trihydrate.
[0043] Step 2: Take 1 g of magnesium carbonate trihydrate from step 1, mix it with 0.06 g of citric acid in 100 mL of deionized water by ultrasonic and mechanical stirring, then place it in a three-necked flask, react at 80 ° C for 7 hours, cool it naturally to room temperature, filter it, wash it with deionized water, and dry it at 50 ° C for 12 hours to obtain a basic magnesium carbonate nanofiber adsorbent.
[0044] Example 3
[0045] A method for preparing a basic magnesium carbonate nanofiber adsorbent comprises the following steps:
[0046] Step 1: Add 50 mL of 2.25 mol / L potassium carbonate solution to 50 mL of magnesium sulfate solution. 2+ CO3 in potassium carbonate solution 2− The molar ratio is 1:1, the solvents of the magnesium sulfate solution and the potassium carbonate solution are both deionized water, and then the reaction is stirred for 1 hour. After the reaction is completed, it is filtered and washed with deionized water to a pH value of 7.0, and then dried at 50°C for 12 hours to obtain magnesium carbonate trihydrate.
[0047] Step 2: Take 1 g of magnesium carbonate trihydrate from step 1, mix it with 0.04 g of citric acid in 16 mL of deionized water by ultrasonic and mechanical stirring, then place it in a three-necked flask, react it at 70 ° C for 18 hours, cool it naturally to room temperature, filter it, wash it with deionized water, and dry it at 50 ° C for 12 hours to obtain a basic magnesium carbonate nanofiber adsorbent.
[0048] Example 4
[0049] A method for preparing a basic magnesium carbonate nanofiber adsorbent comprises the following steps:
[0050] Step 1: Add 50 mL of 2.25 mol / L potassium carbonate solution to 50 mL of magnesium chloride solution. 2+ CO3 in potassium carbonate solution 2− The molar ratio is 1:1, the solvents of the magnesium chloride solution and the potassium carbonate solution are both deionized water, and then the reaction is stirred for 2 hours. After the reaction is completed, it is filtered and washed with deionized water to a pH value of 7.0, and then dried at 50°C for 12 hours to obtain magnesium carbonate trihydrate.
[0051] Step 2: Take 1 g of magnesium carbonate trihydrate from step 1, mix it with 0.1 g of citric acid in 20 mL of deionized water by ultrasonic and mechanical stirring, then place it in a three-necked flask, react it at 95 ° C for 6 hours, cool it naturally to room temperature, filter it, wash it with deionized water, and dry it at 50 ° C for 12 hours to obtain a basic magnesium carbonate nanofiber adsorbent.
[0052] Comparative Example 1
[0053] The preparation steps are the same as those in Example 1, except that magnesium carbonate trihydrate is replaced by anhydrous magnesium carbonate, and the steps include:
[0054] Take 2 g of anhydrous magnesium carbonate and 0.08 g of citric acid in 100 mL of deionized water by ultrasonic and mechanical stirring, then place it in a three-necked flask, react at 80 ° C for 8 hours, cool naturally to room temperature, filter, wash with deionized water, and dry at 50 ° C for 12 hours to obtain the product.
[0055] Comparative Example 2
[0056] The preparation steps are the same as those in Example 1, except that magnesium carbonate trihydrate is replaced by 414 type basic magnesium carbonate, comprising the following steps:
[0057] Take 2g of 414 type basic magnesium carbonate and 0.08g of citric acid in 100mL of deionized water by ultrasonic and mechanical stirring, then place it in a three-necked flask, react at 80°C for 8h, cool naturally to room temperature, filter, wash with deionized water, and dry at 50°C for 12h to obtain the product.
[0058] Examples 1 to 4 of the present invention all prepared basic magnesium carbonate nanofiber adsorbents with good stability and good adsorption capacity for norfloxacin. The basic magnesium carbonate nanofiber adsorbents of Examples 1 and 2 are used as examples for research, and compared with the products of Comparative Examples 1 and 2. The specific research methods and results are as follows:
[0059] 1. Adsorption experiment of norfloxacin using the basic magnesium carbonate nanofiber adsorbent of Example 1:
[0060] S1. Weigh 120 mg of norfloxacin and dissolve it in 1 L of deionized water to prepare a 120 mg / L norfloxacin aqueous solution.
[0061] S2. Weigh 5 mg of the basic magnesium carbonate nanofiber adsorbent of Example 1 and disperse it in 100 mL of a norfloxacin aqueous solution to conduct an adsorption experiment at a temperature of 25° C. for 1 h.
[0062] S3. Centrifuge the suspension after adsorption, and measure the concentration of norfloxacin in the obtained supernatant, so as to measure the adsorption efficiency and adsorption capacity of norfloxacin.
[0063] 2. Adsorption experiment of norfloxacin using the basic magnesium carbonate nanofiber adsorbent of Example 2:
[0064] S1. Weigh 100 mg of norfloxacin and dissolve it in 1 L of deionized water to prepare a 100 mg / L norfloxacin aqueous solution.
[0065] S2. Weigh 10 mg of the basic magnesium carbonate nanofiber adsorbent of Example 2 and disperse it in 100 mL of a norfloxacin aqueous solution to conduct an adsorption experiment at a temperature of 25° C. for 3 h.
[0066] S3. Centrifuge the suspension after adsorption, and measure the concentration of norfloxacin in the obtained supernatant, so as to measure the adsorption efficiency and adsorption capacity of norfloxacin.
[0067] 3. Cyclic adsorption experiment of norfloxacin using the basic magnesium carbonate nanofiber adsorbent of Example 2:
[0068] S1. Weigh 100 mg of norfloxacin and dissolve it in 1 L of deionized water to prepare a 100 mg / L norfloxacin aqueous solution.
[0069] S2. Weigh 10 mg of the basic magnesium carbonate nanofiber adsorbent of Example 2 and disperse it in 100 mL of a norfloxacin aqueous solution to conduct an adsorption experiment at a temperature of 25° C. for 3 h.
[0070] S3. Centrifuge the suspension after the adsorption, and measure the concentration of norfloxacin in the obtained supernatant, so as to measure the adsorption efficiency and adsorption capacity of norfloxacin.
[0071] S4. Ultrasonicate the basic magnesium carbonate nanofiber adsorbent obtained by centrifugal separation in ethanol for 1 hour to desorb norfloxacin to obtain a desorbed basic magnesium carbonate nanofiber adsorbent, and then dry the desorbed basic magnesium carbonate nanofiber adsorbent, and repeat steps S2 and S3 to perform a cyclic adsorption experiment.
[0072] 4. Adsorption experiments were conducted on different concentrations of norfloxacin using the basic magnesium carbonate nanofiber adsorbent of Example 2:
[0073] S1. Weigh 100 mg, 120 mg, 140 mg, 180 mg, and 200 mg of norfloxacin respectively, and then dissolve them in 1 L of deionized water to prepare 100 mg / L, 120 mg / L, 140 mg / L, 180 mg / L, and 200 mg / L norfloxacin aqueous solutions.
[0074] S2. Weigh 5 mg of the basic magnesium carbonate nanofiber adsorbent of Example 2 and disperse it in 100 mL of norfloxacin aqueous solution of different concentrations to conduct an adsorption experiment at an adsorption temperature of 25° C. and an adsorption time of 3 h.
[0075] S3. Centrifuge the suspension after adsorption, and measure the concentration of norfloxacin in the obtained supernatant to measure the adsorption capacity of norfloxacin.
[0076] Figure 1 The results show that the basic magnesium carbonate nanofiber adsorbent prepared in Example 1 has a typical fiber morphology, and the diameter of the nanofiber is about 20 nm.
[0077] Figure 2 The results show that the XRD spectrum of the basic magnesium carbonate nanofiber adsorbent prepared in Example 1 is completely consistent with the standard card of 415 basic magnesium carbonate, proving that the product is pure 415 basic magnesium carbonate.
[0078] Figure 3 The results show that the adsorption capacity and adsorption efficiency of norfloxacin by the basic magnesium carbonate nanofiber adsorbent prepared in Example 1 are 2134 mg / g and 92.1%, respectively.
[0079] Figure 4 The results show that the basic magnesium carbonate nanofiber adsorbent prepared in Example 2 has a typical fiber morphology, and the diameter of the nanofibers is about 30 nm.
[0080] Figure 5The results show that the XRD spectrum of the basic magnesium carbonate nanofiber adsorbent prepared in Example 2 is completely consistent with the standard card of 415 basic magnesium carbonate, proving that the product is pure 415 basic magnesium carbonate.
[0081] Figure 6 The results show that the adsorption capacity and adsorption efficiency of norfloxacin by the basic magnesium carbonate nanofiber adsorbent prepared in Example 2 are 932 mg / g and 91.2%, respectively.
[0082] Figure 7 The results show that after 10 cycles of adsorption experiments on norfloxacin using the basic magnesium carbonate nanofiber adsorbent prepared in Example 2, the adsorption capacity before and after adsorption does not change much, and the basic magnesium carbonate nanofiber adsorbent has good stability.
[0083] Figure 8 The results show that the adsorption capacity of the basic magnesium carbonate nanofiber adsorbent prepared in Example 2 in 100 mg / L, 120 mg / L, 140 mg / L, 180 mg / L and 200 mg / L norfloxacin aqueous solutions are 1862 mg / g, 2133 mg / g, 2382 mg / g, 2755 mg / g and 2828 mg / g, respectively. The basic magnesium carbonate nanofiber adsorbent shows a high adsorption capacity for norfloxacin.
[0084] Fig. 9 The results show that the adsorption of norfloxacin by the basic magnesium carbonate nanofiber adsorbent prepared in Example 2 conforms to the Langmuir isotherm adsorption model, and the fitting results show that the maximum adsorption amount of norfloxacin by type 415 basic magnesium carbonate is 3333.33 mg / g.
[0085] Table 1 is a comparison data of the maximum adsorption amount of norfloxacin by the basic magnesium carbonate nanofiber adsorbent of the present invention and the adsorption amount of norfloxacin by the prior art norfloxacin adsorbent.
[0086] Table 1 Comparison of the maximum adsorption capacity of basic magnesium carbonate nanofiber adsorbent and the prior art norfloxacin adsorbent
[0087]
[0088] Corresponding references in Table 1:
[0089] [1] Ma, Y. Q.; Zhao, N.; Wei, Y. F.; Wang, S.; Liu, D.; Yuan, P.Efficient adsorption and separation of norfloxacin from water by allophaneaerogel microspheres. Sep. Purif. Technol., 2023, 27, 124808. https: / / doi.org / 10.1016 / j.seppur.2023.124808。
[0090] [2] Sharma, P.; Sharma, M.; Laddha, H.; Gupta, R.; Agarwal, M. Non-toxic and biodegradable κ-carrageenan / ZnO hydrogel for adsorptive removal ofnorfloxacin: Optimization using response surface methodology. Int. J. Biol.Macromol., 2023, 238, 124145. https: / / doi.org / 10.1016 / j.ijbiomac.2023.124145。
[0091] [3] Yang, Y. X.; Zhong, Z. P.; Li, J. F.; Du, H. R.; Li, Z. Y.Efficient with low-cost removal and adsorption mechanisms of norfloxacin,ciprofloxacin and ofloxacin on modified thermal kaolin: experimental andtheoretical studies. J. Hazard. Mater., 2022, 430, 128500. https: / / doi.org / 10.1016 / j.jhazmat.2022.128500。
[0092] [4] Tang, J.; Wang, L. J.; Qin, W. W.; Qing, Z. L.; Du, C.; Xiao, S.H.; Yan, B. F. High reusability and adsorption capacity of acid washedcalcium alginate / chitosan composite hydrogel spheres in the removal ofnorfloxacin. Chemosphere, 2023, 335, 139048. https: / / doi.org / 10.1016 / j.chemosphere.2023.139048。
[0093] [5] Yang, H. M.; Wang, S. C.; Liu, Y. X.; Hu, Y.; Shen, W. B. ZIF-67grows in chitosan-rGO hydrogel beads for efficient adsorption of tetracyclineand norfloxacin. Sep. Purif. Technol., 2024, 330, 125208. https: / / doi.org / 10.1016 / j.seppur.2023.125208。
[0094] [6] Poddar, K.; Sarkar, D.; Sarkar, A. Norfloxacin adsorption bytorrefied coco peat biochar as a novel adsorbent in a circular economyframework. Environ. Res., 2024, 251, 118711. https: / / doi.org / 10.1016 / j.envres.2024.118711。
[0095] [7] Wu, J. Q.; Wang, T. S.; Liu, Y. Y.; Tang, W.; Geng, S. Y.; Chen,J. W. Norfloxacin adsorption and subsequent degradation on ball-millingtailored N-doped biochar. Chemosphere, 2022, 303, 135264. https: / / doi.org / 10.1016 / j.chemosphere.2022.135264。
[0096] [8] Wan Y. B.; Liu, X.; Liu, P. L.; Zhao, L.; Zou, W. H. Optimizationadsorption of norfloxacin onto polydopamine microspheres from aqueoussolution: Kinetic, equilibrium and adsorption mechanism studies. Sci. TotalEnviron., 2018, 639, 428~437. https: / / doi.org / 10.1016 / j.scitotenv.2018.05.171。
[0097] [9] Sun, M.; Yang, Y. K.; Huang, M. L.; Fu, S. K.; Hao, Y. Y.; Hu, S.Y.; Lai, D. L.; Zhao, L. Adsorption behaviors and mechanisms of antibioticnorfloxacin on degradable and nondegradable microplastics. Sci. TotalEnviron., 2022, 807, 151042. https: / / doi.org / 10.1016 / j.scitotenv.2021.151042。
[0098]
[10] Yan, B.; Niu, CH Adsorption behavior of norfloxacin and siteenergy distribution based on the Dubinin-Astakhov isotherm. Sci. TotalEnviron., 2018, 631~632, 1525~1533. https: / / doi.org / 10.1016 / j.scitotenv.2018.03.119.
[0099] The results in Table 1 show that compared with the existing norfloxacin adsorbent, the basic magnesium carbonate nanofiber adsorbent has a better adsorption effect on norfloxacin and takes less time to reach adsorption equilibrium, and has greater advantages in adsorption capacity and efficiency.
[0100] and Fig.10 and Fig.11 In contrast, only magnesium carbonate trihydrate as a reactant reacting with citric acid can produce basic magnesium carbonate nanofiber adsorbent with nanofiber morphology. Under the same reaction conditions, anhydrous magnesium carbonate and 414 basic magnesium carbonate cannot generate nanofiber morphology under the action of citric acid.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a basic magnesium carbonate nanofiber adsorbent, characterized in that: The steps include: Magnesium carbonate trihydrate is used as a reactant, and magnesium carbonate trihydrate and citric acid are mixed in deionized water. The free magnesium ions in the citric acid chelate reaction system are used to form basic magnesium carbonate nanofiber crystal nuclei, so that the magnesium carbonate trihydrate reacts under the regulation of citric acid and is converted into a basic magnesium carbonate nanofiber adsorbent with a nanofiber morphology; the basic magnesium carbonate nanofiber adsorbent is composed of MgCO3, Mg(OH)2 and H2O in a molar ratio of 4:1:5; and the diameter of the basic magnesium carbonate nanofiber adsorbent is 3nm~70nm; The mass ratio of citric acid to magnesium carbonate trihydrate is 0.04-0.1:1; the mass ratio of magnesium carbonate trihydrate to deionized water is 0.01-0.06:1; The reaction conditions are: stirring the reaction at 70°C~95°C for 6h~18h.
2. The method for preparing a basic magnesium carbonate nanofiber adsorbent according to claim 1, characterized in that: Magnesium carbonate trihydrate is prepared according to the following steps: using soluble magnesium salt and soluble carbonate as raw materials, mixing the soluble magnesium salt and the soluble carbonate in deionized water and reacting them, and then filtering and washing with water until neutral to obtain magnesium carbonate trihydrate.
3. The method for preparing a basic magnesium carbonate nanofiber adsorbent according to claim 2, characterized in that: Soluble magnesium salts Mg 2+ CO3 with soluble carbonates 2− The molar ratio is 1:
1.
4. The method for preparing a basic magnesium carbonate nanofiber adsorbent according to claim 2, characterized in that: The reaction conditions are: stirring the reaction at room temperature for 0.5h~2h.
5. A basic magnesium carbonate nanofiber adsorbent obtained by the preparation method according to any one of claims 1 to 4.
6. Use of the basic magnesium carbonate nanofiber adsorbent according to claim 5 in preparing a norfloxacin adsorbent.
Citation Information
Patent Citations
Basic magnesium carbonate, production method and use of the same
US20050129606A1
Complexes of magnesium carbonate microparticles and fibers as well as processes for preparing them
US20190047872A1